An oral history of workers' education in Pennsylvania's anthracite coal mining region: Min Matheson and the ILGWU - Ken Wolensky (Adult Education Research Conference, 1994)
Min Matheson led a grass roots workers' education movement for the LDGWU in Pennsylvania's coal region from 1944 to 1963. Part of her story is told here utilizing oral history to provide insight as to the history of adult education and social change.